2020
DOI: 10.1016/j.psychsport.2020.101675
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a 7-week dance (RCT) PE curriculum with different teaching pedagogies and levels of cognitive challenge to improve working memory capacity and motor competence in 8–10 years old children

Abstract: Efficacy of a 7-week dance (RCT) PE curriculum with different teaching pedagogies and levels of cognitive challenge to improve working memory capacity and motor competence in 8-10 years old children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 51 publications
0
36
0
3
Order By: Relevance
“…These findings are in line with previous reports that creative dance training significantly influenced EF in children (Yetti et al, 2019) and with findings that a street dance program significantly improved cognitive flexibility, inhibition and working memory in preschool children (Shen et al, 2020). Oppici et al (2020) gave support in their finding that dance practice coupled with a high cognitive challenge improved working memory in children. A very recent study has also reported that an 8-week dance training improved inhibitory control and working memory in primary school children (Rudd et al, 2021), although the current study is the only evidence of the effect of an aerobic dance program, specifically, on working memory, inhibition and cognitive flexibility in children of primary school ages.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These findings are in line with previous reports that creative dance training significantly influenced EF in children (Yetti et al, 2019) and with findings that a street dance program significantly improved cognitive flexibility, inhibition and working memory in preschool children (Shen et al, 2020). Oppici et al (2020) gave support in their finding that dance practice coupled with a high cognitive challenge improved working memory in children. A very recent study has also reported that an 8-week dance training improved inhibitory control and working memory in primary school children (Rudd et al, 2021), although the current study is the only evidence of the effect of an aerobic dance program, specifically, on working memory, inhibition and cognitive flexibility in children of primary school ages.…”
Section: Discussionmentioning
confidence: 92%
“…When practiced by children, dance may be an effective strategy for engaging children’s cognitive development (Giguere, 2011). Existing school opportunities for focusing on cognitively engaging PA have improved children’s selective attention (Kulinna et al, 2018), and dance interventions during primary school PE classes have improved children’s working memory capacity (Oppici et al, 2020). One recent study reported that an 8-week dance training improved inhibitory control and working memory capacity in primary school children (Rudd et al, 2021), but van den Berg et al (2019) found no evidence of any cognitive benefit to children’s practicing dance 10 minutes a day for nine weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 11 investigations with a total of 2176 people were included in this study, with 2053 subjects in the final data analysis, with mixed genders and ages ranging from 4 to 12 years. A total of seven RCTs [ 23 , 34 , 36 , 37 , 38 , 39 , 40 ] and four studies [ 21 , 24 , 35 , 41 ] were clustered RCTs. In total, seven studies were carried out in Europe, one in America, two in Asia, and one in Australia.…”
Section: Resultsmentioning
confidence: 99%
“…From an affective perspective, children with high movement competence have been found to have higher perceived competence (Barnett et al, 2011;Liong et al, 2015;Duncan et al, 2018) which is important because children who feel confident whilst participating in PE are more likely to enjoy involvement, and consequently feel intrinsically motivated to continue effort and participation in all forms of physical activity. From a cognitive perspective, the ability to perform complex movement skills is positively associated with higher-order cognitive skills, i.e., core executive functions: working memory, inhibitory control and cognitive flexibility (Van Der Fels et al, 2015;Oppici et al, 2020), that allow children to manage their thoughts, actions and emotions in order to accomplish everyday tasks, and also to plan, organize and manage their time effectively. The development of complex movement skills through well-designed PE lessons can act as a 'carrier' of higher-order cognitive skill learning beyond those achieved through traditional classroom-based activities (Mavilidi et al, 2018).…”
Section: Introduction Physical Literacy and Physical Educationmentioning
confidence: 99%